2017
DOI: 10.1080/15548627.2017.1380124
|View full text |Cite
|
Sign up to set email alerts
|

RUBCN/rubicon and EGFR regulate lysosomal degradative processes in the retinal pigment epithelium (RPE) of the eye

Abstract: Macroautophagy/autophagy is an intracellular stress survival and recycling system whereas phagocytosis internalizes material from the extracellular milieu; yet, both pathways utilize lysosomes for cargo degradation. Whereas autophagy occurs in all cells, phagocytosis is performed by cell types such as macrophages and the retinal pigment epithelial (RPE) cells of the eye where it is supported by the noncanonical autophagy process termed LC3-associated phagocytosis (LAP). Autophagy and LAP are distinct pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 67 publications
(142 reference statements)
4
58
0
Order By: Relevance
“…Receptor-mediated phagocytosis was required for mTORC1 activation, which could not be achieved by phagocytosis of latex beads. During the revision of this manuscript, Ferguson’s group similarly reported that S6K phosphorylation can be stimulated by POS phagocytosis in RPE-J cells (36). Their data independently validate POS-induced mTORC1 activation in the RPE.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Receptor-mediated phagocytosis was required for mTORC1 activation, which could not be achieved by phagocytosis of latex beads. During the revision of this manuscript, Ferguson’s group similarly reported that S6K phosphorylation can be stimulated by POS phagocytosis in RPE-J cells (36). Their data independently validate POS-induced mTORC1 activation in the RPE.…”
Section: Discussionmentioning
confidence: 97%
“…Starvation stimulates RPE autophagy in mice and suppresses POS degradation (36), suggesting that autophagy and LAP may counteract each other. mTORC1 directly phosphorylates ULK1 at Ser 758 (50) to suppress macroautophagy.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that two independent autophagy pathways support diurnal waste clearance in the RPE and both are finely regulated by circadian and non‐circadian processes, with a daily induction that relies on and occurs after the peak period of POS disk‐shedding and can be evoked by a light pulse (Kim et al , ; Muniz‐Feliciano et al , ). Although our understanding of the regulation of autophagy pathways has improved, a gap remains in our understanding on how the diurnal activation of both lysosomal biogenesis and function is generated, maintained, and successively repressed daily upon a switch from dark to light conditions in the RPE.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the daily internalization of POS, particularly in aged RPE, adds another factor which requires regulation between LAP, canonical autophagy, and phagocytosis to achieve homeostatic balance. Indeed, under starvation, RPE cells have been shown to activate autophagy in favor of phagocytosis . The central role played by lysosomes under these conditions is therefore of growing interest.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, under starvation, RPE cells have been shown to activate autophagy in favor of phagocytosis. [67] The central role played by lysosomes under these conditions is therefore of growing interest. For instance, elimination of CRYBA1/βA3/A1-crstallin which regulates endo-lysosomal acidification, disrupted both autophagy, and phagocytosis.…”
Section: Discussionmentioning
confidence: 99%